Studying a crack initiation in terms of elastic oscillations in stress strain rock mass - Sdvyzhkova, О.; Golovko, Yu.; Dubytska, M.; Klymenko, D. (Розробка родовищ, 2016)
Purpose.Deriving the criterion of a crack (joint) initiating under simultaneous effect of the rock stress state and elastic oscillations generated by an external source is the research purpose. Determining the quantitative relations to estimate the contribution of oscillations to crack initiation and creating a theoretical basis for the improvement of rock burst forecasting technique is a goal as well.
Methods. The brittle failure theory and a time-space approach are applied to determine a critical length of initiating cracks depending on stress level and amplitude-frequency characteristics of acoustic oscillations. Analysis of experimental data and comparison with the numerical results are carried out.
Findings. Quantitative ratios between the critical length of the crack, the stress intensity factor, oscillation amplitude and frequency are determined. It is shown that there are such values of the oscillation frequencies at which the critical crack length is especially sensitive to the amplitude alteration. The increase in the oscillation amplitude initiates starting the crack with small length. Numerical estimation is made for close-grained sandstone using such characteristics as crack resistance factor and Rayleigh’ wave velocity and tensile strength. Increasing the amplitude twice at the frequency of 1145 Hz causes the triple reduction of the starting crack length. Numerical results correlate with in situ data related to acoustic predicting the dynamic phenomena in the rock mass. Цель. Определить критерий страгивания трещины в породной среде при одновременном воздействии внутренних напряжений в породном массиве и акустических колебаний, генерируемых внешним источником, а
также получить количественные соотношения для оценки влияния колебаний на процесс страгивания трещины
и создать теоретическую основу для совершенствования метода акустического прогноза.
Методика. Применение теории хрупкого разрушения в пространственно-временной постановке для получения количественных соотношений между критической длиной страгиваемой трещины и амплитудночастотными характеристиками колебаний. Сравнение численных результатов с данными экспериментального
прогноза динамических явлений.
Результаты. Даны количественные соотношения между критической длиной трещины, квазистатическим
напряжением, амплитудой, и частотой упругих колебаний в породном массиве. Показано, что существуют частоты колебаний, на которых критическая длина трещин особо чувствительна к изменению амплитуды. Так,
например, для песчаника увеличение амплитуды колебаний в 2 раза на частоте 1145 Гц приводит к уменьшению длины страгиваемых трещин в 3 раза. Численные результаты коррелируют с экспериментальными данными акустического прогноза динамических явлений в породном массиве. Мета. Визначити критерій зрушування тріщини у породному середовищі при одночасному впливі внутрішніх напружень у породному масиві й акустичних коливань, що генеруються зовнішнім джерелом, а також
отримати кількісні співвідношення для оцінки впливу коливань на процес страгування тріщини та створити
теоретичну основу для вдосконалення методу акустичного прогнозу.
Методика. Застосування теорії крихкого руйнування у просторово-часовій постановці для отримання кількісних співвідношень між критичною довжиною тріщини, що стартує, та амплітудно-частотними характеристиками
коливань. Порівняння чисельних результатів з даними експериментального прогнозу динамічних явищ.
Результати. Надані кількісні співвідношення між критичною довжиною тріщини, квазістатичним напруженням, амплітудою і частотою пружних коливань у породному масиві. Показано, що існують частоти коливань, на яких критична довжина тріщин особливо чутлива до зміни амплітуди. Так, наприклад, для пісковику
збільшення амплітуди коливань у 2 рази на частоті 1145 Гц призводить до зменшення довжини тріщин, що
стартують, у 3 рази. Чисельні результати корелюють з експериментальними даними акустичного прогнозу динамічних явищ у породному масиві.